Transitioning out of a figure skating career in Finland : A qualitative study - Shephard, S. (Haaga-Helia University of Applied Science, 2021)
In recent years there has been a growing interest in the implications of athletic career transitions and the post-career adjustment of athletes. The purpose of this thesis is to find out what kind of experiences Finnish figure and synchronized skaters have had in their transition processes, the support they had available to them, as well as the kind of support they wish to have had at the time.